The quality of ayurvedic zephyr made using innovative technology - Vyshnevska, Lyudmyla; Frolova, Natalia; Voitsekhіvskyi, Volodymyr; Horbatiuk, Svitlana (My University, 2024)
Дані досліджень про вплив рослинної сировини на органолептичні та фізико-хімічні властивості аюрведичного зефіру представлений в статті. Встановлено, що вживання прянощів і порошків рослин покращує якість і підвищує біологічну та аюрведичну цінність продуктів. Отримані результати слід враховувати при складанні раціонів збалансованого харчування людей різних вікових категорій.

Research data on the effect of plant raw materials on the organoleptic and physicochemical properties of ayurvedic marshmallows are presented in the article. It has been established that the use of spices and vegetable powders improves the quality and increases the biological and ayurvedic value of products. The obtained results should be taken into account when creating balanced nutrition diets for people of different age categories.
Keywords: аюрведична кулінарія; доша; прянощі; порошок овочевий; зефір; ayurvedic cooking; dosha; spices; vegetable powder; marshmallow; кафедра технології ресторанної і аюрведичної продукції